'The most atypical experience of my life': The experience of popular music festivals on cruise ships. (September 2017) - Cashman, David
This article considers the growing phenomenon of music festivals on cruise ships. These commercial events, partnerships between event companies and shipping lines, celebrate a particular genre of music and occur aboard a cruise ship. The views of 138 festivalgoers primarily concentrated within six festivals were considered. According to these sources, the festival experience of these events is centred on three factors: live performances, interaction with fellow festivalgoers and star musicians (collectively referred to as 'ship fam'), and interaction with the constructed space of the cruise ship. Cruise ship music festivals are a different type of music festival, still occurring within festival space, but within the mobile experiential cocoon of a cruise ship.